The influence of gambler's fallacy and financial literacy on generation z's investment decisions in the digital era - Fathur Baihaqi Marzuki; Muhamad Daffa Azriel; Prima Naomi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Financial decisions play a significant role in determining an individual’s economic well-being, especially in today’s digital era, where access to financial services and information is much easier. Among Generation Z, who were born amidst technological advancements and have instant access to various digital platforms, financial decisions are often influenced by various factors, including cognitive biases such as the Gambler’s Fallacy (Justyanita & Agustin, 2023). The Gambler’s Fallacy refers to the false belief that past random outcomes will influence future random outcomes (He, 2022). Although this phenomenon is more commonly associated with gambling, its impact is also seen in everyday financial behaviour.